Anti-emetic Drugs for Prophylaxis of Postoperative Nausea and Vomiting After Craniotomy: An Updated Systematic Review and Network Meta-Analysis - Chen, Yijing; Chang, Jing (Frontiers in Medicine, 2020)
Background: There is uncertainty about the effect of antiemetic drugs (AED) for the prophylaxis of postoperative nausea and vomiting (PONV) after craniotomy. In this study, we assessed the effectiveness and safety of AED for PONV. Methods and Findings: We searched online databases including the Cochrane Library, PubMed, Wiley, Elsevier Science Direct, Ovid LWW, and Springer for publications from 1985 to June 2018. Adults undergoing craniotomy with the prophylactic use of at least one AED were included. The primary outcomes were the incidence of postoperative nausea (PON) and postoperative vomiting (POV) during the first and second day. A total of 1,433 participants from 17 clinical trials were enrolled in this Network Meta-Analysis (NMA). Compared to placebo, ramosetron was the most effective treatment for PON 24 h after surgery (OR = 0.063, 95% Crl: 0.006–0.45), with a 69.2% probability. On the other hand, for POV, droperidol was the best treatment during the first 2 h with a 71.1% probability (OR = 0.029, 95% Crl: 0.003–0.25); while fosaprepitant was the most effective treatment at 0–24 h (OR = 0.027, 95% Crl: 0.007–0.094; 66.9% probability) and 0–48 h (OR = 0.036, 95% Crl: 0.006–0.18; 56.6% probability). Besides, ramosetron showed a significantly higher incidence of complete response (OR = 29. 95% Crl: 1.4–6.5e + 02), as well as lower requirement for rescue AED (OR = 0.022, 95% Crl: 0.001–0.2). Granisetron was associated with the lowest incidence of headache and excessive sedation. Conclusions: Compared with placebo, ramosetron appears to be the best prophylactic treatment for PON 24 h after craniotomy, with higher complete responses. Fosaprepitant appears to be the most effective prophylaxis option for POV on the first 0–24 and 0–48 h. Both may be better applied in combination with perioperative dexamethasone. These findings may guide clinicians to provide improved pharmacological prophylaxis for PONV after craniotomy with fewer adverse effects.